Bigger Calves from Doing Higher Resistance Training Volume? - Kassiano, Witalo; Costa, Bruna Daniella de Vasconcelos; Kunevaliki, Gabriel; Lisboa, Felipe; Tricoli, Ian; Francsuel, Jarlisson; Lima, Luis; Stavinski, Natã; Cyrino, Edilson S. (International Journal of Sports Medicine, 2024)
We compared the effects of different weekly calf training sets on muscle size changes. Sixty-one untrained young women performed a calf training program for 6 weeks, 3 d·wk–1, with differences in resistance training volume. The participants were randomly assigned to one of the three groups: 6-SET, 9-SET, and 12-SET weekly calf training sets. The calf raise exercise was performed in sets of 15–20 repetitions maximum. The muscle thickness measurements of medial gastrocnemius (MG), lateral gastrocnemius (LG), and soleus (SOL) were taken via B-mode ultrasound. We used the sum of the three-muscle thickness as a proxy for the triceps surae (TSSUM). The 12-SET group elicited greater increases than the 6-SET in LG (6-SET=+ 8.1% vs. 12-SET=+ 14.3%; P=0.017), SOL (6-SET=+ 6.7% vs. 12-SET=+ 12.7%; P=0.024), and TSSUM (6-SET=+ 6.9% vs. 12-SET=+ 12.0%; P=0.005), but there was no significant difference in MG changes (6-SET=+ 6.6% vs. 12-SET=+ 9.9%; P=0.067). There were no significant differences when comparing 9-SET vs. 6-SET and 12-SET (P≥0.099). Although all groups experienced calf muscle hypertrophy, our results suggest that the higher dose range may optimize triceps surae muscle size gains.
Keywords: strength training; dose-response relationship; muscle growth; gastrocnemius; soleus